Antioxidant and Proliferative Activities of Bupleuri Radix Extract Against Serum Deprivation in SH-SY5Y Cells - Seo, Mi Kyoung; Cho, Hye Yeon; Lee, Chan Hong; Koo, Kyung Ah; Park, Yong Ki; Lee, Jung Goo; Lee, Bong Ju; Park, Sung Woo; Kim, Young Hoon (Psychiatry investigation, 2013)
Bupleuri Radix (BR) is a major component of several Oriental herbal medicines used to treat stress and mental illness. There are evidences that antidepressant drugs modulate oxidative damage implicated in the pathophysiology of neuropsychiatric disorder, including depression. The aim of the present study was to investigate antioxidant and proliferative effects of BR against oxidative stress induced by serum deprivation in SH-SY5Y cells. We examined the antioxidant effects of BR on a number of measures, including cell viability, formation of reactive oxygen species (ROS), superoxide dismutase (SOD) activity and levels of both Bcl-2 and Bax. We also investigated the effects of BR on cell proliferation using the bromodeoxyuridine (BrdU) assay, and used Western blot analysis to measure changes in expression of the cell cycle phase regulators. 1) Serum deprivation significantly induced the loss of cell viability, the formation of ROS, the reduction of SOD activity, down-regulation of Bcl-2 expression and up-regulation of Bax expression. However, BR extract reversed these effects in dose-dependent manner. 2) Serum deprivation significantly reduced cell proliferation. Western blot analysis revealed that serum deprivation significantly decreased cyclinD1 and phosphorylated retinoblastoma (pRb) expression, and increased p27 expression. On the other hand, BR dose dependently reversed these effects. This study suggests that aqueous extract of BR may exert potent antioxidant effects and also play an important role in regulating cell cycle progression during neurogenesis. These effects of BR may be a potentially important mechanism of antidepressant underlying the observed antioxidant and proliferative effects.